Brain dynamics of visual anticipation during spatial occlusion tasks in expert tennis players. (March 2023) - Costa, Sergio; Berchicci, Marika; Bianco, Valentina; Croce, Pierpaolo; Di Russo, Francesco; Quinzi, Federico; Bertollo, Maurizio; Zappasodi, Filippo
Abstract: Stimulus identification and action outcome understanding for a rapid and accurate response selection, play a fundamental role in racquet sports. Here, we investigated the neurodynamics of visual anticipation in tennis manipulating the postural and kinematic information associated with the body of opponents by means of a spatial occlusion protocol. Event Related Potentials (ERPs) were evaluated in two groups of professional tennis players (N = 37) with different levels of expertise, while they observed pictures of opponents and predicted the landing position as fast and accurately as possible. The observed action was manipulated by deleting different body districts of the opponent (legs, ball, racket and arm, trunk). Full body image (no occlusion) was used as control condition. The worst accuracy and the slowest response time were observed in the occlusion of trunk and ball. The former was associated with a reduced amplitude of the ERP components likely linked to body processing (the N1 in the right hemisphere) and visual-motor integration awareness (the pP1), as well as with an increase of the late frontal negativity (the pN2), possibly reflecting an effort by the insula to recover and/or complete the most correct sensory-motor representation. In both occlusions, a decrease in the pP2 may reflect an impairment of decisional processes upon action execution following sensory evidence accumulation. Enhanced amplitude of the P3 and the pN2 components were found in more experienced players, suggesting a greater allocation of resources in the process connecting sensory encoding and response execution, and sensory-motor representation. Highlights: Tennis experts were more accurate than less expert players when predicting the landing position of tennis shots.. Trunk Occlusion reduced the amplitudes of ERP components N1, pP1 and pP2 but increased late frontal negativity (pN2). Greater accuracy in expert players was associated with larger amplitude of components pN2 and P3. Source reconstruction of ERP components was consistent with ERP and fMRI studies of body processing and visual cognition.